A cascade model and initial exploration of co-production processes underpinning the ecosystem services of geothermal areas. (December 2020) - Cook, David; Davíðsdóttir, Brynhildur; Malinauskaite, Laura
Abstract: This paper presents the first study in the academic literature to explore the various stages in the formation of geothermal ES and their interactions between the biosphere and anthroposphere. This is achieved through the development of the first ES cascade model in the academic literature specific to geothermal ES, which integrates the four main stages of co-production: value attribution, mobilisation of ES potential, value appropriation, and commercialisation. In so doing, conceptual understanding of human-environment relationships and processes in the context of geothermal ES are deepened. Examples from the academic and grey literature demonstrate that realisation of the full spectrum of benefits from geothermal areas often demands the mobilisation of various forms of physical capital. Reaping the benefits of provisioning ES, such as heat and minerals, or formal recreational experiences, such as geothermal spas, necessitates human interventions. Opportunities of likely value have to be attributed, with resources being mobilised in order to plan and research prospectivity, then benefits appropriated with a view to their commercialisation. Large-scale, industrial projects, especially geothermal power plants in high enthalpy fields, also constitute an overlap between anthropogenic and ecological systems, often leading to ES trade-offs, especially due to visual and noise impacts on the surroundings. Depending on the sociocultural context, multiple and conflicting value domains may be impacted by such ventures, justifying the adoption of a pluralist approach to valuation and use of integrated decision-support platforms to aid decision-makers. Highlights: First CICES classification of geothermal ecosystem services. Four co-production stages: attribution, mobilisation, appropriation and commercialisation. Benefits include formal recreational experiences and provisioned minerals. Impacts from commercialisation include noise and visual effects. Impacts to multiple value domains imply need for value pluralism in decision-making.